2021
DOI: 10.1186/s13578-021-00562-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomic analysis of eutopic endometrium and ectopic lesions of adenomyosis

Abstract: Background Adenomyosis (AM) is a common benign chronic gynaecological disorder; however, the precise pathogenesis of adenomyosis is still poorly understood. Single-cell RNA sequencing (scRNA-seq) can uncover rare subpopulations, explore genetic and functional heterogeneity, and reveal the uniqueness of each cell. It provides us a new approach to reveal biological issues from a more detailed and microscopic perspective. Here, we utilize this revolutionary technology to identify the changes of ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…The Cell Ranger software pipeline (version 3.1.0) provided by 10 × Genomics was used to demultiplex cellular barcodes, map reads to the genome and transcriptome using the STAR aligner, and down-sample reads as required to generate normalised aggregate data across samples, producing a matrix of gene counts versus cells [ 59 , 60 ]. We processed the UMI count matrix using the R package Seurat (version 3.0.0) to remove low-quality cells and likely multiples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cell Ranger software pipeline (version 3.1.0) provided by 10 × Genomics was used to demultiplex cellular barcodes, map reads to the genome and transcriptome using the STAR aligner, and down-sample reads as required to generate normalised aggregate data across samples, producing a matrix of gene counts versus cells [ 59 , 60 ]. We processed the UMI count matrix using the R package Seurat (version 3.0.0) to remove low-quality cells and likely multiples.…”
Section: Methodsmentioning
confidence: 99%
“…We then annotated the clusters based on the average expression of curated gene sets of the following major cell types: epithelial cells ( EPCAM, KRT19, KRT18, KRT5, KRT15 ), macrophages/monocytes ( CD68, MS4A4A, MS4A7 ), T cells ( CD2, CD3D/E/G ), MAST cells ( CD117, TPSB2, TPSAB1 ), NK cells ( TRDC, KLRC1 ), neutrophils ( CD16, CD66 ), ECs ( AQP1, MYCT1, CDH5, PECAM1 ), and FBs ( COL1A1, COL3A1, COL1A2 )(representative marker reference from: http://biocc.hrbmu.edu.cn/CellMarker/ and https://panglaodb.se/search.html ) [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…Liu et al proved the theory about the migration and invasion of the endometrium into the myometrium. Their results indicated that the inhibition of EET (epithelial–endothelial transition) and VM formation (vascular-mimicry formation) may be a potential strategy for adenomyosis management [ 42 ].…”
Section: Adenomyosis and Risk Of Malignant Transformationmentioning
confidence: 99%
“…Further studies indeed corroborated the hypothesis of invasiveness, as adenomyotic glands appear to resemble those of eutopic endometrium and most likely originate from them [ 18 ]. Moreover, single-cell transcriptomic data detected a clear upturn in genes related to cell motility and cancer-like features in adenomyosis [ 19 ]. It has also been hypothesized that estrogen itself drives EMT in adenomyosis, although other studies have proposed inflammation-associated factors as mediators of this process [ 16 , 20 , 21 ].…”
Section: Hypotheses On the Origin Of Uterine Adenomyosismentioning
confidence: 99%